The Importance of Iron To Support Optimum Cognitive Development - Sekartini, Rini (Indonesian Nutrition Association, 2021)
The fetal brain anatomy development starts during the last trimester of pregnancy and continue in early months of life. This critical process makes it vulnerable to insufficient nutrition, while brain growth continues into adulthood, micronutrient status can affect functioning beyond childhood. Iron is an important nutrient for the production and growth of cells in the immune and neural systems. Iron deficiency (ID) is the most common nutrient deficiency in the world, affecting about half of all pregnant women and their offspring. Iron deficiency anemia has long been believed to have an effect on the central nervous system. Iron deficiency in late trimester and in newborn leads to abnormal cognitive function and emotional control that may continue in adulthood. In summary, despite some evidence that iron supplementation enhances cognitive performance. Evidence of the role of iron in brain development and the effect of iron deficiency or iron supplementation on early development is uncertain.